Peran Budaya Kerja, Lingkungan Kerja, Disiplin Kerja, Kompensasi Dan Keahlian Terhadap Kinerja Karyawan Pada PT. Mega Briquette Ungaran - Sukardi Sukardi (Serat Acitya, 2018)
The purpose of this study was to determine the effect of work culture, work environment, work discipline, compensation, and expertise on the performance of company employees. Based on this, this research takes the title "The Role of Work Culture, Work Environment, Work Discipline, Compensation and Expertise on Employee Performance of PT. Mega Briquette Ungaran ”. The population is all employees of the company PT. Mega Briquette Ungaran Semarang Regency in the production, packing, and administration section of 129 employees. Sampling with random sampling techniques, namely determining the number of samples by taking randomly by giving the existing population the same opportunity to be sampled. Determining the number of samples using the Slovin formula obtained 56 respondents. The data used are primary data obtained by distributing questionnaires. Data analysis using linear regression analysis. Based on the results of the study, it is concluded that work culture has a significant effect on the performance of the Company's employees at PT. Mega Briquette Ungaran Semarang Regency. The work environment has a significant effect on the performance of the employees of the company PT. Mega Briquette Ungaran Semarang Regency. Work discipline has a significant effect on the performance of the employees of the company PT. Mega Briquette Ungaran Semarang Regency. Compensation has a significant effect on the performance of the employees of the company PT. Mega Briquette Ungaran Semarang Regency. Expertise has a significant effect on the performance of the employees of the company PT. Mega Briquette Ungaran Semarang Regency. Keywords: work culture, work environment, work discipline, compensation, skills, and employee performance